A Study on the Application of Accounting Bases in Village Government Entities - Herdiyana, Deni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study seeks to critically assess the most suitable accounting basis for implementation within the framework of Village Government Accounting Standards, with a focus on enhancing the governance and accountability mechanisms of Village Fund management and reporting. Employing a qualitative desk study approach, the research draws upon relevant regulatory frameworks and scholarly literature addressing accounting basis applications under Government Accounting Standards (SAP). The findings suggest that the Cash Toward Accrual (CTA) basis represents the most appropriate model for village-level financial reporting, as it offers more comprehensive and informative financial disclosures compared to the traditional cash basis, while also adhering to the principles of transparency and accountability. Moreover, the adoption of the CTA basis is financially more feasible than the full accrual basis, particularly given the resource constraints commonly faced at the village level. To facilitate effective implementation, the study recommends structured technical assistance and awareness programs prior to the formal adoption of the CTA-based accounting system, thereby minimizing potential operational challenges.